CLOUD DEPLOYMENT MODELS FOR RESILIENCE INTERNET DISASTER RECOVERY: A REVIEW - Anigbogu, Gloria N; Ituma Chinagolum; Anigbogu, S. O.; Anigbogu, K. S. (International Journal of Innovations in Engineering Research and Technology, 2021)
Organizations of all sizes require safeguarding of their data on regular basis, which makes disaster recovery and backup procedures, a much desired responsibility. This paper reviewed the various cloud deployment models for resilience internet disaster recovery in cloud computing environment. The work was able to show the relevance of deployment of appropriate disaster recovery models in cloud computing environment that can help to improve quality of service and customer confidence in their service provider.